A study to assess prevalence of treatment default among lung cancer patients registered at a tertiary care hospital - Dave, Lokendra; Mishra, Vikas; Gupta, Rakesh C.; Gour, Neeraj; Shrivastava, Nishant; Kuldeep, Rajveer S.; Chaudhary, Meenakshi (International Journal of Research in Medical Sciences, 2018)
Background: Lung cancer is among the five main types of cancer leading to overall cancer mortality contributing about 1.3 million deaths/year globally. Completion of treatment among lung cancer patients is one of key factor for the survival and longevity of patients. So, we have tried to find out prevalence of treatment default through this study. Methods: This is a cross-sectional descriptive study (including retrospective secondary and prospective primary data) using data base of patients of primary lung cancer diagnosed between 1st January 2006 to 31st December 2012 in indoor and outdoor of department of Respiratory Medicine, J.L.N. Medical College, Ajmer, a tertiary level hospital and teaching center. Results: Incidence of lung cancer is significantly higher among young female (10.23%) as compared to young male (8.74 %). Whereas in older group number of male suffering from lung cancer than female. Total 269 (20.7%) patients defaulted from planned treatment and most of them ultimately drop-out from chemotherapy cycles. Intercycle delay of 2 weeks-1m commonly seen. Conclusions: It provides future implication to researchers to explore reasons of these defaults and drop outs so that more evidences can be generated in this direction for the ultimate betterment of lung cancer patients.